Interactive rendering of light scattering in dust molecules using particle systems. (2018) - Ali, Hatam H.; Sunar, Mohd Shahrizal; Kolivand, Hoshang
In this paper introduces a technique for rendering effect of the volumetric lighting in dusty atmosphere using particle systems. Despite numerous techniques has been proposed for rendering these effects but still lack realism in the interactive applications. This technique is based on the sampling planes to compute radiance transport equation and use dynamic model of the dust. The scattering of light is computed by using fragment shaders and 2D texture by making use of the graphics hardware, while using ParticleEngine technique generates the dust. The technique is efficient and accurate to mimic a realistic scenes have effect such as scattering of light in dust molecules. In addition to, volumetric shadows are created resulting of density and size particles within participating media. Therefore, scattering of light is generated in presence dusty media that lead to provide visual clue closer to realistic.